The twelfth general elections in Malaysia - Mokhtar, Tunku Mohar (IIUM Press, 2008)
The twelfth general elections in Malaysia resulted in the ruling coalition (Barisan Nasional, BN) losing its two-thirds majority in Parliament. Denying the BN its sought after two-thirds majority is what the opposition parties were campaigning for. Additionally, they won five state assemblies. The electorate voted on the basis of “bread and butter” issues which were highlighted by the ruling coalition as well as the opposition parties.